SOG'LIQNI SAQLASH MUASSASALARIDA STRATEGIK MENEJMENT: AHOLI SALOMATLIGI KO'RSATKICHLARI VA DEMOGRAFIK JARAYONLARNING TIBBIY-IJTIMOIY TAHLILI - Rajabova Nodira Mahmud qizi; Sohibov Oybek Mardonovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The global demographic transition and the increasing burden of diseases necessitate a shift from traditional reactive management in healthcare facilities to proactive governance based on pharmaco-economic value. Within the scope of the research object, the impact of socio-demographic factors on financial toxicity and DALY (Disability-Adjusted Life Years) indicators in regional healthcare systems was evaluated. Logistic regression analysis of retrospective data from N=1450 patients demonstrated that in institutions implementing targeted screening and digital monitoring, the coverage of risk groups reached 78.4%, while budget expenditures for advanced-stage treatments were reduced by a factor of 3.5 (p < 0.05). Based on empirical findings, a multi-vector management model relying on socio-demographic stratification and the reduction of inpatient reliance was developed. This strategic approach ensures the long-term financial sustainability of medical institutions.